Molecular and Mechanical Mechanisms Regulating Ductus Arteriosus Closure in Preterm Infants - Ovalı, Fahri (Frontiers in Pediatrics, 2020)
Failure of ductus arteriosus closure after preterm birth is associated with significant morbidities. Ductal closure requires and is regulated by a complex interplay of molecular and mechanical mechanisms with underlying genetic factors. In utero patency of the ductus is maintained by low oxygen tension, high levels of prostaglandins, nitric oxide and carbon monoxide. After birth, ductal closure occurs first by functional closure, followed by anatomical remodeling. High oxygen tension and decreased prostaglandin levels mediated by numerous factors including potassium channels, endothelin-1, isoprostanes lead to the contraction of the ductus. Bradykinin and corticosteroids also induce ductal constriction by attenuating the sensitivity of the ductus to PGE2. Smooth muscle cells of the ductus can sense oxygen through a mitochondrial network by the role of Rho-kinase pathway which ends up with increased intracellular calcium levels and contraction of myosin light chains. Anatomical closure of the ductus is also complex with various mechanisms such as migration and proliferation of smooth muscle cells, extracellular matrix production, endothelial cell proliferation which mediate cushion formation with the interaction of blood cells. Regulation of vessel walls is affected by retinoic acid, TGF-β1, notch signalling, hyaluronan, fibronectin, chondroitin sulfate, elastin and vascular endothelial cell growth factor (VEGF). Formation of the platelet plug facilitates luminal remodeling by the obstruction of the constricted ductal lumen. Vasa vasorum are more pronounced in the term ductus but are less active in the preterm ductus. More than 100 genes are effective in the prostaglandin pathway or in vascular smooth muscle development and structure may affect the patency of ductus. Hemodynamic changes after birth including fluid load and flow characteristics as well as shear forces within the ductus also stimulate closure. Current pharmacological treatment for the closure of a patent ductus is based on the blockage of the prostaglandin pathway mainly through COX or POX inhibition, albeit with some limitations and side effects. Further research for new agents aiming ductal closure should focus on a clear understanding of vascular biology of the ductus.